Communicative competence as perceived by adults with severe speech impairments associated with cerebral palsy. - Bedrosian JL; Hoag LA; Johnson D; Calculator SN (Journal of Speech, Language & Hearing Research, 1998)
The effects of aided message length (single-word vs. phrase-generated messages) and partner feedback (presence vs. absence of expanded message repetitions) on perceptions of the communicative competence of an adult augmentative and alternative communication (AAC) system user were examined. Subjects consisted of 12 nonambulatory adults with severe speech impairments associated with cerebral palsy. Four scripted videotaped conversational conditions involving the AAC system user and a typically speaking partner were employed to manipulate the two independent variables. A balanced incomplete block design was used. Following each viewing, subjects completed a questionnaire designed to assess the communicative competence of the AAC system user. Results indicated that neither independent variable had an impact on the subjects' ratings of communicative competence. Findings are compared with those from an earlier investigation, and clinical implications are discussed.